Pathological anatomy study of a hemorrhagic disease in four (4) pigs - Vale Echeto, Oswaldo; Vásquez, Donitzi; Camacho Bracho, Jesús; Vale Oviedo, Oswaldo; Oviedo de Vale, María (Revista Científica de la Facultad de Ciencias Veterinarias, 1970)
Many diseases occur in pigs causing widespread hemorrhages around the world. Among them are viral or bacterial such as, Classical Swine Fever (C S F) which is produced by a Pestivirus (RNA), Togavirus group of the Flaviviridae family, besides African Swine Fever (ASF) produced by an Iridovirus and wgich has not been diagnosed in Venezuela, according to the literature. Among bacterial diseases are Salmonellosis and Erysipellosis, being the latter uncommon in Venezuela. In this paper, the morphological aspects of the hemorrhagic disease in four pigs are described. The reported lesions are not too dissimilar to those occurring in cases of C S F, which is characterized by affecting many vital organs, producing death in many pigs. C S F often follows an acute course characterized by generalized hemorrhages, with high morbidity and mortality, but it may be chronic, in that case clinical signs and lesions are often minimal or absent. The disease in naturally infected pigs produces lethal lesions causing death in many unvaccinated animals as well as in vaccinated pigs. The gross and microscopic changes of a hemorrhagic systemic disease in four (4) cases under study are reported from two naturally infected unvaccinated pigs and two postvaccinated animals against C S F. Pathologic changes are correlated with clinical signs and the most revelant morphological gross changes and histopathology are reported from naturally infected unvaccinated and postvaccinated pigs. The hemorrhagic lesions reported in vital organs highly resemble and are very similar to those morphologic changes occurring in C S F, although, other hemorrhagic viral or bacterial diseases induced a more severe and different pattern in lesions though being hemorrhagic. Despite lab tests (Elisa) were not determined in this work, they must be ruled out to show the etiological agent of C S F in spite of the typical and very similar morphological changes reported in this paper.